Adapting to Finland through professional football : perceptions of players and coaches - Swarts, Christoffer M. J. (2014)
The present study explores how football migrants (foreign professional football / soccer players) perceive the adaptation process in Finland. Globalization and legislation have made it easier for football players to work abroad. The amount of football migrants in Finland is increasing each year. The internationalization of Finnish football requires study. Successful adaptation has a positive outcome on a migrant, which will increase the chances of personal, and thus in the case of football, team success. This thesis is a qualitative study of five football migrants, who are interviewed based on thematic, semi structured face-to-face conversations in Finland. The following research questions for this study are used to get insight in the adaptation process of football migrants: (1) how do football migrants feel about the possibilities in Finland to fulfil their dreams and ambitions?; (2) What are the impressions of their adaptation process in Finland?; (3) What are the football migrant’s perceptions of their own intercultural communication skills?; And, (4) how internationally orientated are Finnish football organizations, according to football migrants? The key finding of this study is that football migrants have a hard time adapting to Finland through professional football: local football clubs are not ready to work with foreigners in order to achieve full potential. In addition, there are too many differences between the Finnish communication style and the one of the football migrant, which causes frictions on the football pitch. Although Finnish football has become more international during the last years, there is a lack of focus on intercultural communication competence.